Pengaruh Model Teams Games Tournament (TGT) Terhadap Minat Belajar Siswa Kelas III Mata Pelajaran Bahasa Jawa MI PSM Sulursewu - Hidayah, Khayatul; Permata, Santy Dinar; Mashuri, Anwas (Civiliza Publishing, Indonesia., 2023)
The aim of the research carried out is as follows: To determine the implementation of the Teams Games Tournament (TGT) type cooperative learning model for class III MI PSM Sulursewu students on Javanese language learning content. The research was conducted at MI PSM Sulursewu, Paron, Ngawi, using quantitative experimental methods with a population of all students (226 people) and a sample of 27 class III students. Data collection was carried out through a questionnaire with 35 statements using a modified Likert scale of 1-4 to avoid ambiguity in the answers. In this research, the results of data analysis and paired sample t-test show that there is a significant influence from the use of the TGT model on the learning interest of class III students in Javanese language subjects at MI PSM Sulursewu. Before treatment, students' interest in learning was low, but after treatment, there was a significant increase in students' interest in learning, indicating that the TGT model had a positive effect on their interest in learning.